Does COVID -19 Changed Education Forever? - Khattak, Nuzhat S. (International Journal of Pathology, 2022)
Covid-19 is arguably an event that has changed many things for Humans such as social interactions etc. The most important change that the Covid-19 made in this century was that it changed the mode of instruction/teaching from in-person to remote or online. Countries around the globe had no idea what was about to hit them and once the pandemic started gaining momentum governments could see no other option but to close down everything. Everything started closing down from markets to offices, schools, and universities. After the closure of educational institutes throughout the world, there was a need to resume educational activities and the only option available was to conduct online classes.